2021
DOI: 10.2214/ajr.20.25315
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-90 Hepatic Radioembolization for Advanced Chemorefractory Metastatic Colorectal Cancer: Survival Outcomes Based on Right- Versus Left-Sided Primary Tumor Location

Abstract: The publication of this Accepted Manuscript is provided to give early visibility to the contents of the article, which will undergo additional copyediting, typesetting, and review before it is published in its final form. During the production process, errors may be discovered that could affect the content of the Accepted Manuscript. All legal disclaimers that apply to the journal pertain. The reader is cautioned to consult the definitive version of record before relying on the contents of this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Wu et al, 14 in a RS, analyzed data from 99 patients, and recorded that higher risk of death is associated with: right-sided CRC (HR = 1.74; P = 0.03); lung-shunt fraction > 10% (HR = 1.89; P = 0.02); alkaline phosphatase > 150 U/L (HR = 1.90; P = 0.004); total bilirubin > 1.0 mg/dL (HR = 1.94; P = 0.02); CEA levels > 20 ng/mL (HR = 1.90; P = 0.02); liver-tumor volume percentage > 15% (HR = 1.96; P = 0.002); no post-Y90-RE systemic therapy (HR = 3.18; P < 0.001). The multivariate analysis showed that the only independent predictors associated with a higher survival are: right-sided colon cancer, alkaline phosphatase > 150 U/L, total bilirubin > 1.0 mg/dL, liver-tumor volume percentage > 15%, and not-receiving post-Y90-RE systemic therapies.…”
Section: Clinical Predictorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Wu et al, 14 in a RS, analyzed data from 99 patients, and recorded that higher risk of death is associated with: right-sided CRC (HR = 1.74; P = 0.03); lung-shunt fraction > 10% (HR = 1.89; P = 0.02); alkaline phosphatase > 150 U/L (HR = 1.90; P = 0.004); total bilirubin > 1.0 mg/dL (HR = 1.94; P = 0.02); CEA levels > 20 ng/mL (HR = 1.90; P = 0.02); liver-tumor volume percentage > 15% (HR = 1.96; P = 0.002); no post-Y90-RE systemic therapy (HR = 3.18; P < 0.001). The multivariate analysis showed that the only independent predictors associated with a higher survival are: right-sided colon cancer, alkaline phosphatase > 150 U/L, total bilirubin > 1.0 mg/dL, liver-tumor volume percentage > 15%, and not-receiving post-Y90-RE systemic therapies.…”
Section: Clinical Predictorsmentioning
confidence: 99%
“…In 10 of the 14 papers selected for the present SR are reported details of the Y90-RE range, median, and mean administered activity (Table 2). [5][6][7][8][9][10][11][12][13][14] In 4 of these studies are described the values of minimum administered activity, ranging from 0.20 to 0.81 GBq, maximum values, ranging from 1.68 to 9.50 GBq, and the median administered activity values, ranging from 1.08 to 1.89 GBq with an average value of the medians of 1.53 GBq (Fig. 2).…”
Section: Administered Activitymentioning
confidence: 99%
See 3 more Smart Citations